Mind Mapping Training’s Effects on Divergent Thinking Skills: Detection Based on EEG Data - Ting Liu; Zhisheng Wang; Hao Yu (Applied Sciences)
As a translation strategy, mind mapping has a positive influence on the development of students’ divergent thinking skills. However, research on how mind mapping affects divergent thinking has primarily relied on traditional testing methods, which mainly focus on completed translation tasks. There is still a lack of research using dynamic and procedural experimental methods. An electroencephalogram (EEG) is one of the most effective tools for identifying and analyzing cognitive processing. In this study, we utilized EEG data to explore the effects of mind mapping on divergent thinking skills, with a primary focus on the dynamics of the alpha band power, which is closely related to divergent thinking. The participants were university students learning foreign languages in Dalian, China. One group received foreign language translation teaching integrated with mind mapping training (experimental group), while the other group received regular foreign language translation teaching (control group). The task-related alpha band power of participants engaged in divergent thinking tasks shows that participants in the experimental group exhibited superior divergent thinking skills, as evidenced by greater elevations in alpha band power within the anterior frontal lobe (M = 0.582, SD = 0.301), frontal lobe (M = 0.312, SD= 0.103), frontocentral lobe (M = 0.183, SD = 0.256), and temporal lobe (M = 0.205, SD = 0.176). In addition, they displayed significantly greater alpha band activity in the right cerebral hemisphere (M = 0.418, SD = 0.271), further highlighting the unique neural patterns linked with divergent thinking. The empirical results indicate that mind mapping training is an effective method for enhancing students’ divergent thinking skills.